1996
DOI: 10.1007/bf00436657
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis in Rome, Italy

Abstract: This report presents the results of a study conducted between 1985 and 1994 on onychomycosis observed in the city of Rome. Six thousand six hundred and eighty eight patients were examined during this period. Among them 1,762 (26.3%) were affected by fungal nail infections. Because the etiologic agents could not be isolated in 105 cases (6%), the results refer to 1,657 subjects (24.8% of the total), presenting with positive microscopic and cultural examinations. Thirty eight patients (2.3%) had onychomycosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 40 publications
5
25
2
3
Order By: Relevance
“…In contrast, studies carried out by other investigators have demonstrated a greater prevalence of dermatophytes as etiological agents of onychomycosis 7,19−21) . Based on Rubio Calvo et al 21) , Mercantini 20) , Iaannidou et al 22) , Mügge 7) and El Sayed et al 19) , the prevalence of onychomycosis with dermatophytic origin was 14.7%, 23.7%, 52%, 68% and 77.1%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, studies carried out by other investigators have demonstrated a greater prevalence of dermatophytes as etiological agents of onychomycosis 7,19−21) . Based on Rubio Calvo et al 21) , Mercantini 20) , Iaannidou et al 22) , Mügge 7) and El Sayed et al 19) , the prevalence of onychomycosis with dermatophytic origin was 14.7%, 23.7%, 52%, 68% and 77.1%, respectively.…”
Section: Discussionmentioning
confidence: 94%
“…Onychomycosis of fingernails is most 8 prevalent in females while toenail infection is common in male patients 1,57 . Candida species is the dominant cause of onychomycosis in women and dermatophytes is the principal cause of this condition in men 35,51 . According to CROCCO et al 13 , candidiasis expresses the variety of relations that occur between the host and autochthon microbiota, ranging from commensalism to systemic disease.…”
Section: Resultsmentioning
confidence: 99%
“…Adhikari et al, also found a higher prevalence of onychomycosis in similar age groups [19]. In contrast, Velez et al, and Mercantini et al, reported higher prevalences among adults who were over 50 years of age [16,20]. The increased prevalence of onychomycosis at young ages could be because of occupation related trauma, cosmetic awareness and shoe wearing habits.…”
Section: Discussionmentioning
confidence: 99%